Instability characteristics of surrounding rock and surrounding rock control technology of deep coal roadway crossing the fault: a case study of Zhuxianzhuang coal mine - Huaibin Li; Weipeng Pan; Xinzhu Hua; Bo Luan; Zujun Huang (Geomatics, Natural Hazards & Risk)
To prevent severe damage to the surrounding rock of the roadway under the high ground pressure within deep mining, the stress evolution of the surrounding rock was studied, and the surrounding rock control technology in the II1057 roadway of Zhuxianzhuang Coal Mine before and after passing fault was conducted through theoretical analysis, numerical simulation and engineering practice. The results show that when the roadway is advanced to 20 m away from the fault, the surrounding rock is broken, cracks are generated at 2.56 m above the roof, and the advance abutment pressure of the roadway is 17–20 MPa. Through the borehole detection technology, the development of the internal cracks in the surrounding rock was observed, and the surrounding rock control technology scheme (the advanced grouting in front of the roadway and the active support of rock bolt + anchor cable + M steel belt + steel beam + metal mesh) was proposed. The engineering practice shows that the roof separation, roof-to-floor convergence and sidewall convergence are greatly reduced, and the mechanical properties of the surrounding rock of the roadway are greatly improved, leading to the effective control of the deformation of the roadway surrounding rock.